THE KINETICS BOTH OF GROWTH AND METABOLITE PRODUCTION OF X.CAMPESTRIS USING OF 4% LIQUID SUGAR SUBSTRATE FROM CASSAVA HYDROLISATE - Djenar, Nancy Siti; Mulyono, Edi Wahyu Sri (Jurnal Bahan Alam Terbarukan, 2017)
X. campestris is aerobic bacteria producing extracellular biopolymers (EPS, extracellular polysaccharide) known as xanthan gum. To determine the technology and the process conditions appropriate to the formation of this product, therefore the understanding of both the kinetics of growth and metabolite production of bacteria is needed. In this research, to assess the growth of X. campestris using the method of calculation of dry cell weight. For determining the kinetics of production of metabolite used substrates of 4% liquid sugar  from cassava starch hydrolysate. From this research was showed that X. campestris maximum growth in NB medium obtained in about 58thhour, at the growth rate of about 0.04 g / hour, stationary phase obtained at the 60th hour with a maximum dry cell weight of 2.7688 g/L and specific growth rate (μ) of X. campestris amounted to 0.043 hour-1. Based on the kinetic curves both on growth and its metabolite production, X.campestris has non-growth associated product pattern. In this case the production of  xanthan gum  occured after cell growth stopped then  its product is a secondary metabolite with highest amount  of 3.73 g / L at 102nd hour, ie the 4th day of fermentation. Overall of this research indicated that  Nutrient Broth (NB) may be used for the growth of X. campestris. But based on the value of μ above, the rate of cell reproduction was still low. Liquid sugar can be used as a substrate to produce xanthan gum. However to increase its productivity, there should be an addition of other carbon or energy and nitrogen sources.